The Definition of Specific-Purpose English Language Competences Needed in Border Control and their Development Potentials I. The Issues of Defining Specific- Purpose Language Competences - Borszéki, Judit (Magyar Rendészet, 2017)
The aim of this series of papers is to present modern methods of linguistics and language pedagogy concerning specific-purpose language competences and, applying them to English for Border Guards, to describe the English competences to be developed at language courses for border guards in EU member states and to explore the prospects for their improvement. The first part of the series discusses the dilemmas and methodology related to the definition of specific-purpose language competences and to needs analyses, indispensable for language course design in general and their application in the context of English for Border Guards. In the form of a CEF Professional Profile, it also presents the findings of a series of interviews conducted with border guards involved in FRONTEX Joint Operations on how they use